2013
DOI: 10.1002/hec.3013
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Pricing in Emerging Markets: Effects of Income, Competition, and Procurement

Abstract: This paper analyzes determinants of ex-manufacturer prices for originator and generic drugs across countries. We focus on drugs to treat HIV/AIDS, TB, and malaria in middle and low-income countries (MLICs), with robustness checks to other therapeutic categories and the full income range of countries. We examine the effects of per capita income, income dispersion, competition from originator and generic substitutes, and whether the drugs are sold to retail pharmacies versus tendered procurement by non-governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 25 publications
1
52
0
Order By: Relevance
“…Another possibility would be to price drugs differentially so that they are cheaper in low-income countries [23]. This approach has a limited value in the case of advanced treatments because they are deemed costly even in the wealthiest nations.…”
Section: Issues With Affordable Pricingmentioning
confidence: 99%
“…Another possibility would be to price drugs differentially so that they are cheaper in low-income countries [23]. This approach has a limited value in the case of advanced treatments because they are deemed costly even in the wealthiest nations.…”
Section: Issues With Affordable Pricingmentioning
confidence: 99%
“…Patients in such self-pay markets lack the financial protection of insurance but also avoid its distorting effects on prices. However, other factors -including uncertain product quality and skewed income distributions --contribute to higher drug prices than might occur in well-functioning markets [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Efficient pricing in selfpay markets requires that: regulatory systems assure that all drugs, including for generic copies, meet specified quality standards; consumers or their agents are reasonably informed about drug quality and prices; and manufacturers can price-discriminate within countries that have highly skewed income distributions. In practice, these conditions are not met in many MLICs, leading to pricing above marginal cost and static efficiency loss that potentially outweighs the contribution of high prices to profits and dynamic efficiency [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In the public sector, inefficiency in procurement system has been a major shortcoming. A comprehensive study has observed that entrance of a new generic manufacturer in a thriving generic market would result in only a nominal decrease in price, while competitive tendering and efficient procurement would translate to marked decrease [51] . Sri Lanka with a sound procurement system has been able to purchase medicines at low prices.…”
Section: Resultsmentioning
confidence: 99%
“…Factors such as asymmetry of information, minimal involvement of consumers in choosing the products, and direct relation of the products with morbidity and mortality do not allow the pharmaceutical market to be solely left to market forces without detrimental effects on health [51] . There is little doubt about whether the quality aspect of pharmaceuticals should be regulated; with the quality factor having the potential of hazardous impact on health, it is mandatory across countries for manufacturers and products to meet certain quality requirements.…”
Section: Resultsmentioning
confidence: 99%